Biomechanical properties of hip cartilage in experimental animal models - Constantinides, Georgios; Athanasiou, Kyriacos A.; Agarwal, Animesh (My University, 1995)
The material properties of normal adult articular cartilage were determined in the femoral head and acetabulum of baboons, dogs, and bovines, and were compared with those of normal human hip cartilage. In situ creep and recovery indentation experiments were performed using an automated creep indentation apparatus. To curvefit the entire creep curve, a numerical algorithm based on biphasic finite element methods and nonlinear optimization was developed. This effort represents the first successful use of 100% of the creep indentation curve to obtain the mechanical properties of normal articular cartilage. The results show that material properties of articular cartilage exhibit significant topographical variations in the femoral head and acetabulum, and between these two bone structures. Furthermore, significant differences exist in the mechanical properties of hip cartilage among the 4 species. Specifically, in all species the smallest aggregate modulus is found in the inferior aspect of the femoral head. Among all species, human hip cartilage is the stiffest in all test sites; bovine tissue is the softest. Human tissue has the smallest Poisson's ratio and permeability in all test sites. The aggregate modulus of human hip cartilage is closely resembled by that of baboon hip cartilage. Anatomically, canine and baboon hips exhibit similar characteristics to the human hip joint; the bovine hip joint is distinctly different. Based on this study's data, the baboon represents the most appropriate animal model of normal human hip articular cartilage.
Keywords: Biomechanics; Cartilage; Cattle; Mathematical models